Lipid Antigen Presentation by CD1b and CD1d in Lysosomal Storage Disease Patients - Pereira, Catia S. (Front Immunol, 2019)
The lysosome has a key role in the presentation of lipid antigens by CD1 molecules. While defects in lipid antigen presentation and in invariant Natural Killer T (iNKT) cell response were detected in several mouse models of lysosomal storage diseases (LSD), the impact of lysosomal engorgement in human lipid antigen presentation is poorly characterized. Here, we analyzed the capacity of monocyte-derived dendritic cells (Mo-DCs) from Fabry, Gaucher, Niemann Pick type C and Mucopolysaccharidosis type VI disease patients to present exogenous antigens to lipid-specific T cells. The CD1b- and CD1d-restricted presentation of lipid antigens by Mo-DCs revealed an ability of LSD patients to induce CD1-restricted T cell responses within the control range. Similarly, freshly isolated monocytes from Fabry and Gaucher disease patients had a normal ability to present α-Galactosylceramide (α-GalCer) antigen by CD1d. Gaucher disease patients' monocytes had an increased capacity to present α-Gal-(1-2)-αGalCer, an antigen that needs internalization and processing to become antigenic. In summary, our results show that Fabry, Gaucher, Niemann Pick type C, and Mucopolysaccharidosis type VI disease patients do not present a decreased capacity to present CD1d-restricted lipid antigens. These observations are in contrast to what was observed in mouse models of LSD. The percentage of total iNKT cells in the peripheral blood of these patients is also similar to control individuals. In addition, we show that the presentation of exogenous lipids that directly bind CD1b, the human CD1 isoform with an intracellular trafficking to the lysosome, is normal in these patients.